Negative life events and mental health problem: The importance of coping strategy - Siti Nor Yaacob,; Fam, Jia Yuin *; Muslihah Hasbullah,; Zarinah Arshat,; Rumaya Juhairi, (Universiti Putra Malaysia Press, 2019)
Exposure to negative life events can be extremely stressful for adolescents from divorced families and effective coping strategy can help to alleviate their stress. The current study examined the relationship between negative life events, coping strategy, and mental health problem among adolescents from divorced families. This study also explored the moderating role of coping strategy in the relationship. The sample of this study was 480 adolescents from divorced families, which were identified through multistage cluster sampling. The Malay Version of 12-Items General Health Questionnaire was implemented to measure mental health problem among the adolescents. The Brief Adolescent Life Event Scale was implemented to measure negative life events among adolescents. Brief Coping Orientation for Problem Experiences (COPE) was implemented to measure coping strategy. The current study revealed that mental health problem was significantly correlated with negative life events (r = 0.498, p < 0.001), maladaptive coping (r = 0.537, p < 0.001), and adaptive coping (r = -0.417, p < 0.001). The results found that both maladaptive (interaction effect = 0.158, p < 0.01) and adaptive coping (interaction effect = -0.150, p < 0.001) as significant moderators in the relationship between negative life events and mental health problem among adolescents. Specifically, the impact of negative life events is less severe when adolescents reported frequent application of adaptive coping. In contrast, negative life events are most detrimental when adolescents reported high reliance on maladaptive coping. The current study demonstrated that the magnitude of the relationship between negative life events and mental health problem is highly depending on the choice of coping strategy. The present study concluded that adaptive coping can effectively mitigate while maladaptive coping exacerbates the adverse impact of negative life events. The findings of this study have practical implications in helping adolescents to bounce back from the negative consequences of parental divorce.